Surveying Complex Samples for 3 Synthetic Elements by Targeted Enrichment - Bergman,Andrew (2025)
Our ability to genetically engineer microorganisms is growing rapidly. We can perform small, precise modifications using techniques such as CRISPR-Cas9 to whole-virome synthesis and/or large genetic insertions. These advances reduces the threshold for synthetic biology to be employed maliciously. Preparations against pandemics or deliberate biological attacks currently rely on taxonomic identification of microorganisms and inference of their pathogenicity. In the modern landscape of bioengineering, taxonomic identification may be misleading as commonly benign microorganisms may be altered to increase their virulence and pathogenicity. Since modern bioengineering can fail to detect harmful microbes, there is a gap in the current methodology. In order to address this gap, this project aims to assess if in-solution hybridization (targeted enrichment) is a feasible approach to identify microorganisms by selectively enriching DNA elements that could indicate synthetic intervention. The approach utilizes a custom bait panel that targets plasmids and antibiotic resistance genes (ARGs). The bait panel was applied to a fecal sample set and a spike-in sample set (where a cell line, VERO E6, is mixed with a concoction of plasmid sequences). The enrichment outcome is preliminarily successful for initial DNA concentrations as low as 2.5e-5 ng. Background depletion works differently well depending on sample set, one of them yielding background sequence reduction from 90% to 10%. Continued experimentation should build upon the exploratory results achieved in this study by validating the results and continuing the optimization of the bait panel.